From Single to Configurable: A Multidimensional Analysis of Drivers of Green Product Purchase Intentio - Wen, Zhiqiang; Zhu, Xiaolin; Dong, Yingli (International Journal of Multidisciplinary Research, 2026)
To investigate the drivers and mechanisms of consumers 'green product purchase intention, this study selects consequence awareness, environmental cognition, incentive policies, collective efficacy, and eco-centrism as independent variables. Using fuzzy set qualitative comparative analysis (fsQCA) and structural equation modeling (SEM), the theoretical model was validated. The results reveal four configurations influencing consumers' green product purchase intention: environment-cognition-driven (social responsibility-led), comprehensive-driven, eco-belief-driven (social responsibility-led), and consequence-awareness-driven collective. These configurations highlight the critical roles of different factors in promoting green product purchase intention, providing valuable insights for policy formulation and corporate marketing strategies.